MENGANALISIS MISKONSEPSI PADA MATERI ALJABAR PADA BUKU MATEMATIKA KELAS VII SEMESTER 1 - Riris Irawati Sinurat; Dea Ananda Claudia Nainggolan; Dosta Ernauli Siregar; Citra Inova Sinaga; Samuel Christoffer Silalahi; Wingston Leonard Sihombing (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is a science that plays a very important role in everyday life. Mastery of mathematical concepts is essential, especially in algebra, which is a fundamental part of mathematics. However, in the algebra material presented in the Grade VII Semester 1 Mathematics textbook, Revised Edition 2016, misconceptions that potentially confuse students have been found. This study uses a descriptive qualitative approach with a literature review method to a=nalyze errors in the presentation of algebra material in the textbook. The analysis reveals several misconceptions in simplifying algebraic fractions, including errors in dividing terms within sums, errors in factoring numerators or denominators, and errors in determining common denominators when adding algebraic fractions. These misconceptions often arise due to the author's carelessness in presenting the material and inappropriate examples, which may confuse students. Therefore, improvements are necessary from the textbook author, and teachers also play a crucial role in providing additional explanations so students can correctly understand algebraic concepts. With these efforts, misconceptions are expected to be minimized, making the learning of algebra material more effective and meaningful.